HUBUNGAN KADAR TIMBAL DARAH DENGAN JUMLAH ERITROSIT PADA IBU MENYUSUI - Dewi Sulistyoningrum; Puja Intan Sartika (Midwifery Care Journal, 2022)
Human health can be affected by heavy metals in the form of lead which have toxic properties and can accumulate in the body. One of the effects of lead exposure is affecting the hematological system by interfering with heme synthesis, and can shorten the life of red blood cells (erythrocytes) which can cause anemia. The purpose of this study was to determine the relationship between blood lead levels and the number of erythrocytes in breastfeeding mothers.This research is an analytic study with a cross sectional design. The population of all breastfeeding mothers who live in the working area of the Bandarhajro Public Health Center Semarang. The number of samples of 30 respondents were taken by purposive sampling technique. Statistical analysis was performed using the Statistical Package For The Social Sciences (SPSS) version 20. The results of this descriptive study showed that the blood lead level of breastfeeding mothers was on average 62.24±26.21 g/dL with a minimum value of 18.39 g/dL and a maximum value of 98.00 g/dL. The results of bivariate analysis showed that there was no significant relationship between blood lead levels and the number of erythrocytes (p = 0.195). All respondents living in the Bandarharjo Semarang area had blood Pb levels exceeding the threshold with an average value of 62.24 g/dL. There was no relationship between the number of erythrocytes and blood Pb levels in breastfeeding mothers (p-value = 0.195)